PENERAPAN MODEL PEMBELAJARAN VISUALIZATION AUDITORY KINESTETIK UNTUK MENINGKATKAN PARTISIPASI DAN PRESTASI BELAJAR - Afendi (DIADIK, 2024)
This study aims to describe the application of the auditory kinesthetic visualization learning model and to describe the effectiveness of the application of the kinesthetic auditory visualization learning model to increase participation and learning achievement of 6th grade students of SDN Gugus 2 Lubuk Pinang's mathematics learning achievement. The research design used was Classroom Action Research (CAR) and Quasi-Experimental Research. The subjects in this study were grade 6 students of SDN Cluster 2 Lubuk Pinang semester 1 for the academic year 2022/2023. The number of students for the PTK class is 17 people, the experimental class is 17 people, the control class is 17 people. The method of collecting data was observation and tests. The research instrument used teacher activity observation sheets, student participation observation sheets and student learning outcomes tests on each material being taught. Data analysis used the average score and tests consisting of a difference test between cycles and a different test of two unrelated samples. The results showed that the visualization auditory kinetic learning model could increase student participation and learning achievement in the 6th grade math content of SDN Gugus 2 Lubuk Pinang